Analisis Faktor-Faktor Disiplin Kerja Karyawan Pada Kantor Koperasi Telekomunikasi Seluler Wilayah Sumbagut Medan - Ummi habibah Sirait; Farida Hanum Siregar (Universitas Medan Area, 2022)
This study aims to determine the description of employee discipline factors at the Office of the Cellular Telecommunications Cooperative at Sumbagut Region Medan. In this study, the employee population worked at the Sumbagut Medan Regional Cellular Telecommunication Cooperative Office was 60 permanent employees. The problem is focused on factors affecting the work discipline of employees at the Office of the Cellular Telecommunications Cooperative at Sumbagut Region Medan. In approaching this problem, a theoretical reference from Hasibuan (2016) is used which states that there are 5 factors that affect the work discipline of employees in an organization, namely goals and abilities, leadership, competence, punitive sanctions and waskat. The data were collected through the dissemination of a work discipline scale to employees of the Office of the Cellular Telecommunications Cooperative at Sumbagut Region Medan and analyzed using descriptive quantitative methods. This study concluded that there was an orderly factor, waskat of 21.25%, then the next factor was compensation of 20.54%, and followed also by a leadership factor of 20.09%, then the goal and ability factor of 19.24% and the lowest factor affecting work discipline was the punishment factor of 18.88%.